GREEN SPIRITUALITY IN HIGHER EDUCATION: SUSTAINABLE GREEN CAMPUS TRANSFORMATION AT THE UNIVERSITY OF JAMBI - Wahyu Iskandar; Saidina Usman; Nori Nopita Sari (International Journal of Education, Language, and Social Science, 2025)
This study aims to see (1) How the concept of Green Spirituality is applied in higher education at the University of Jambi (2) To what extent the impact of sustainable green campus transformation on the environment, students, and the surrounding community. This study uses a descriptive qualitative approach to explore in depth the concept of Green Spirituality in the context of higher education and sustainable green campus transformation at the University of Jambi. Interviews were conducted with key informants who have direct involvement in the implementation of green spirituality values in the campus environment. Participatory observation was applied to directly observe sustainability practices with data analysis techniques in this study using an interactive model. The results of the study show that (1) The concept of Green Spirituality is applied at the University of Jambi through the Unja Lestari program which emphasizes the integration of spiritual, ecological, and social care values in all campus activities. This program encourages the academic community to view the environment as a trust from God that must be maintained through environmentally friendly behavior, such as reducing plastic waste, energy conservation, and greening the campus area (2) The impact of sustainable green campus transformation on the environment in Jambi shows a positive direction that includes ecological, social, economic, and academic aspects. A sustainable green campus also strengthens students' readiness for a green economy-based workforce. The ecological competencies they acquire are crucial assets in the modern job market.